2014
DOI: 10.1163/15707563-00002432
|View full text |Cite
|
Sign up to set email alerts
|

Fecal cortisol content of wild giant pandas (Ailuropoda melanoleuca) to monitor human disturbance level in natural habitats

Abstract: Wild animals are affected by growing human interference in their habitats and inevitably react internally to such stimuli. This study explores inherent physiological parameters to assess the effect of human interference on giant pandas in their wild habitat. Ninety-one fecal samples were collected within four nature reserves on Qinling Mountain. Fecal cortisol determinations were performed by radioimmunoassay. We categorized the intensity of local human disturbance and tested for correlations between the inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…What is more, the average IAP calculated within each buffer showed that the area was influenced by a marked anthropic pressure, which may have affected individual wildcat welfare. The effect of anthropic disturbance on cortisol accumulation has received considerable attention in recent years and has been studied in various species (Rangel-Negrín et al 2009;Zwijacz-Kozica et al 2012;Burbonnais et al 2013;Creel et al 2013;Deng et al 2014;Fourie et al 2015) including tigers (Naidenko et al 2019) and wildcats (Piñeiro et al 2012). For instance, Naidenko et al (2019) compared faecal glucocorticoid levels between two tiger subspecies, the Amur tiger and Bengal tiger living in two extreme habitats.…”
Section: Compared Faecalmentioning
confidence: 99%
See 1 more Smart Citation
“…What is more, the average IAP calculated within each buffer showed that the area was influenced by a marked anthropic pressure, which may have affected individual wildcat welfare. The effect of anthropic disturbance on cortisol accumulation has received considerable attention in recent years and has been studied in various species (Rangel-Negrín et al 2009;Zwijacz-Kozica et al 2012;Burbonnais et al 2013;Creel et al 2013;Deng et al 2014;Fourie et al 2015) including tigers (Naidenko et al 2019) and wildcats (Piñeiro et al 2012). For instance, Naidenko et al (2019) compared faecal glucocorticoid levels between two tiger subspecies, the Amur tiger and Bengal tiger living in two extreme habitats.…”
Section: Compared Faecalmentioning
confidence: 99%
“…A further study performed by Rangel-Negrín et al (2009) showed that forest fragmentation may create long-term stressors for spider monkeys (Ateles geoffroyi yucatanensis) affecting population viabilities. Deng et al (2014) revealed a significant positive correlation between FCM levels recorded in giant pandas (Ailuropoda melanoleuca) and the degree of human disturbance within their habitat. Fourie et al (2015) showed that human impacts on vervet monkeys' (Chlorocebus aethiops) behavioural ecology appeared to be a significant source of stress, especially for males.…”
Section: Compared Faecalmentioning
confidence: 99%
“…Human-related disturbance as a stressor had inconsistent effects on FGs reported in the literature. There was a strong positive correlation between intensity of human disturbance within nature reserves and FGs in giant pandas that tended to avoid settlements and roads (Deng et al, 2014). Similarly, Malcolm et al (2014) found that Asiatic black bears had higher levels of FGs outside nature reserves (closer to human settlements), but in the same study there were lower levels of GCs in roadside faeces.…”
Section: Measuring Long-term Stress In Free-ranging Bearsmentioning
confidence: 73%
“…Ranges and means obtained from all available literature for brown, Asiatic black bears and giant pandas can be found in Table 2. Cortisol metabolites within faeces degrade and may artificially inflate FG measurements over time with exposure to environmental conditions such as rain, sun, wind and ambient temperatures, as has been reported for giant pandas (Deng et al, 2014), mountain goats (Oreamnos americanus) (Dulude-de Broin et al, 2019) and whitetailed deer (Washburn & Millspaugh, 2002). However, tests run by Stetz et al (2013) who collected half of each sampled scat (from grizzly and American black bears) and left the remaining half in its natural setting for 1-28 days, found that degradation effects are not significant over the given timeframe.…”
Section: Measuring Long-term Stress In Free-ranging Bearsmentioning
confidence: 99%
See 1 more Smart Citation